Salidroside alleviates cholestasis-induced liver fibrosis by inhibiting hepatic stellate cells via activation of the PI3K/AKT/GSK-3β signaling pathway and regulating intestinal flora distribution - Wang, Xin; Cao, Shuxia; Huang, Yuan; Li, Liangchang; Xu, Dongyuan; Liu, Lan (Frontiers in Pharmacology, 2024)
Salidroside (SAL), a phenylpropanoid bioactive compound, has various pharmacological properties, including antioxidant, anti-inflammatory, and hepatoprotective effects. However, the pharmacological effects and mechanisms of action of SAL on cholestatic liver injury are unclear. This study investigated the mechanism and effects of salidroside (SAL) on intestinal flora distribution and hepatic stellate cell (HSC) activation in cholestatic hepatic fibrosis. Bile duct ligation was used to cause cholestasis BALB/c mice. The therapeutic efficacy of SAL in liver fibrosis was assessed via serum/tissue biochemical analyses and liver tissue hematoxylin and eosin and Masson staining. Inflammation and oxidative stress were analyzed using enzyme-linked immunosorbent assay and western blotting. HSC were activated in vitro using lipopolysaccharide, and the effects of SAL on HSC migration and inflammatory factor expression were detected via scratch, transwell, and western blotting assays. The effects of SAL on the PI3K/AKT/GSK-3β pathway in vivo and in vitro were detected using western blotting. 16sRNA sequencing was used to detect the effect of SAL on the diversity of the intestinal flora. Ileal histopathology and western blotting were used to detect the protective effect of SAL on the intestinal mucosal barrier. SAL reduces liver inflammation and oxidative stress and protects against liver fibrosis with cholestasis. It inhibits HSC activation and activates the PI3K/AKT/GSK-3β pathway in vitro and in vivo. Additionally, SAL restores the abundance of intestinal flora, which contributes to the repair of the intestinal mucosal barrier, inhibits endotoxin translocation, and indirectly inhibits HSC activation, reversing the course of cholestatic liver fibrosis. SAL inhibits HSC activation through the PI3K/AKT/GSK-3β pathway and improves intestinal flora distribution, thereby protecting and reversing the progression of hepatic fibrosis.